Water or mineral resource? Legal interpretations and hydrosocial configurations of lithium mining in Chile - Flores Fernández, Cristián; Alba, Rossella (Frontiers in Water, 2023)
The advance of electromobility has boosted global demand and interest in lithium. The consequent expansion of lithium mining puts the sustainability of Chile´s Andean salt flats at risk. In these unique ecosystems, lithium is abstracted from mineralized groundwaters, referred to also as brines. This article analyses the legal treatment of brines and its implications in assessing the socioecological impacts of lithium mining projects. For our analysis we draw from scholarship at the intersection between hydrosocial research and critical legal geography. Methodologically, our study is based on interviews and the analysis of legal texts and judicial and administrative claims, including the environmental impact assessment studies of the three single lithium mining projects approved in the country. We show that the interpretation of brines as mining resources supported by mining companies and endorsed by environmental State agencies is based on a legal loophole. We document how such interpretation is operationalized and contested in the environmental impact assessments of three mining projects and other instances. We explore how the same legal loophole could lead to alternative interpretations and relatedly regulatory proposals and discuss their implication for the assessment of socioecological impacts of mining projects. These include first an understanding of brines as hybrids minerals/waters put forward in a recent report commissioned by State agencies, and second an interpretation of brines as a type of water. The latter is in line with the position of some indigenous groups and academics. We conclude with reflections on the implications of our analysis for lithium mining in Chile and beyond.